Low-energy three-body charge transfer reactions with Coulomb interaction in the final state - Sultanov, R. A.; Adhikari, S. K. (Iop Publishing Ltd, 1999)
Three-body charge transfer reactions with Coulomb interaction in the final state are considered within the framework of coordinate-space integro-differential Faddeev-Hahn-type equations within two- and six-state close-coupling approximations. The method is employed to study direct muon transfer in low-energy collisions of the muonic hydrogen H-mu by helium (He2+) and lithium (Li3+) nuclei. The experimentally observed isotopic dependence is reproduced.